Efficacy of propolis supplementation to accelerate healing process and body weight recovery of pulmonary tuberculosis patients - Mahani, Mahani; Sulaeman, Ahmad; Anwar, Faisal; Damanik, Muhamad Rizal Martua; Hardinsyah, Hardinsyah; Ploeger, Angelika (Jurnal Gizi dan Pangan, 2018)
This study aimed to evaluate the pace of curing process and body weight recovery of pulmonary tuberculosis (Tb) patients receiving propolis supplementation. This study was a randomized controlled trial conducted on 50 pulmonary Tb patients that were assigned into three groups as follows: receiving standard-dose antituberculosis drugs (ATDs) + 20 drops of placebo propolis (P0); receiving standard-dose ATDs + 20 drops of propolis with concentration of 6% (P1); and receiving standard-dose ATDs + 20 drops of propolis with concentration of 30% (P2). The results showed that the mean time ratio needed for sputum smear conversion to negative present of acid resitant bacteria in P0, P1 and P2 groups were weeks 10, 8 and 5, respectively. In the second week, mean body weight of P0 and P1 groups decreased by 2.4% and 0.2%, respectively. In contrast, the mean body weight in P2 group increased by 1.5% (p<0.05; Mann-Whitney test). In the same week, mean body mass index (BMI) of P0 and P1 groups decreased by 1.6 and 0.1, respectively. Conversely, the mean BMI of P2 group increased by 0.3. The changes were significantly different (p<0.05). The results conclusively indicated that supplementation of 20 drops of propolis with a concentration of 30% as an adjuvant to standard ATDs for the treatment of pulmonary Tb patients was beneficial to accelerate treatment effect and body weight recovery.